Linguistic Skill and Stimulus-Driven Attention: A Case for Linguistic Relativity - Ansorge, Ulrich; Baier, Diane; Choi, Soonja (Frontiers in Psychology, 2022)
How does the language we speak affect our perception? Here, we argue for linguistic relativity and present an explanation through ‘language-induced automatized stimulus-driven attention’ (LASA): Our respective mother tongue automatically influences our attention and, hence, perception, and in this sense determines what we see. As LASA is highly practiced throughout life, it is difficult to suppress, and even shows in language-independent non-linguistic tasks. We argue that attention is involved in language-dependent processing and point out that automatic or stimulus-driven forms of attention, albeit initially learned as serving a linguistic skill, account for linguistic relativity as they are automatized and generalize to non-linguistic tasks. In support of this possibility, we review evidence for such automatized stimulus-driven attention in language-independent non-linguistic tasks. We conclude that linguistic relativity is possible and in fact a reality, although it might not be as powerful as assumed by some of its strongest proponents.